Traceability in the Dairy Industry in Europe Theory and Practice - Mania, Ignazio (Springer International Publishing, 2018)
This book explores food traceability in raw materials, additives and packing of the dairy sector and it provides an accessible and succinct overview of the new Extended Traceability (ExTra) software. In this work, the authors present several practical examples of extended food traceability for edible products and food-contact materials in the cheese-making industry. Readers will also discover a summary of the existing legal and regulatory requirements for food traceability in Europe. This book will appeal to a wide readership, from academic researchers to professionals and auditors in industry working in quality control, food and packing traceability, and international regulation. .